Structural Equation Modeling in Road Safety Behaviour Integration with Psychological and Spiritual Factors - Mohamad Ghous, Mohd Tarmizi (International Journal of Integrated Engineering, 2019)
Road safety is major concerns in Malaysia. Human errors are the most contributing cause of road accident. Human bad attitude is mainly influenced by their psychology and spiritual aspects. This research is conducted based on those assumption to enhance driver safety behaviour. The main of objective is to identify and analyze the psychological and spiritual factors that contribute to safe driving behaviour. A total of 256 respondents from various type of background were distributed handed with a self-administered questionnaire. Demographic and experience of respondents was analysed using a descriptive statistics. Education level and traffic summons are the only has show significant association to safety driving by Chi-square test at significant level (p<0.05). This finding is demonstrated by correlation analysis that shows attitude of drivers towards safety driving has a significant relation (p<0.05) on psychological factors and spiritual factors. Then, a Structural Equation Modelling (SEM) was performed used to postulate the hypothesis. The structural model showed that psychological and spiritual factors is influenced and would enhance drivers to practice safe driving behaviour, and this might reduces number of road accidents. Therefore, this study will contribute to related agencies as useful guidelines in order to mitigate road safety among drivers.